Litterfall and leaf decomposition in Nothofagus pumilio forests along an altitudinal gradient in Tierra del Fuego, Argentina - Moretto, Alicia Susana (2014)
To achieve a fuller understanding of forest ecosystem functioning, it is necessary to know decomposition dynamics. The objective of this study was to quantify litter production, decomposition and mineralization in Nothofagus pumilio forests, in Tierra del Fuego, Argentina, along an altitudinal gradient during a two-year period and relate them to microclimate conditions and soil properties. We did the research along an altitudinal sequence at 210, 330, 460 and 590 m a.s.l., where climate, soil properties and forest structure were characterized. Litterfall decreased with altitude, and it was highly related with leaf and reproductive organ production. Decomposition decreased with altitude, being associated with microclimate and soil properties rather than with other measured variables, such as leaf chemistry. Values of decomposition constant (k) were influenced by altitude and varied between seasons and years within a given altitude. Nitrogen content increased with altitude in the two-year period, while P content decreased. Decomposition rates allowed us to separate the forest stands according to altitudinal gradients, and their intrinsic abiotic characteristics, which could increase the understanding of the nutrient flux and dynamics in these austral forest ecosystems.